Differential lipid signaling from CD4+ and CD8+ T cells contributes to type 1 diabetes development - Tayleur D. White; Tayleur D. White; Abdulaziz Almutairi; Abdulaziz Almutairi; Abdulaziz Almutairi; Ying Gai-Tusing; Ying Gai-Tusing; Daniel J. Stephenson; Daniel J. Stephenson; Benjamin D. Stephenson; Benjamin D. Stephenson; Benjamin D. Stephenson; et al. (Frontiers in Immunology, 2024)
IntroductionWe reported that Ca2+-independent phospholipase A2β (iPLA2β)–derived lipids (iDLs) contribute to type 1 diabetes (T1D) onset. As CD4+ and CD8+ T cells are critical in promoting β-cell death, we tested the hypothesis that iDL signaling from these cells participates in T1D development. MethodsCD4+ and CD8+ T cells from wild-type non-obese diabetic (NOD) and NOD.iPLA2β+/- (NOD.HET) mice were administered in different combinations to immunodeficient NOD.scid. ResultsIn mice receiving only NOD T cells, T1D onset was rapid (5 weeks), incidence 100% by 20 weeks, and islets absent. In contrast, onset was delayed 1 week and incidence reduced 40%–50% in mice receiving combinations that included NOD.HET T cells. Consistently, islets from these non-diabetic mice were devoid of infiltrate and contained insulin-positive β-cells. Reduced iPLA2β led to decreased production of proinflammatory lipids from CD4+ T cells including prostaglandins and dihydroxyeicosatrienoic acids (DHETs), products of soluble epoxide hydrolase (sEH), and inhibition of their signaling decreased (by 82%) IFNγ+CD4+ cells abundance. However, only DHETs production was reduced from CD8+ T cells and was accompanied by decreases in sEH and granzyme B. DiscussionThese findings suggest that differential select iDL signaling in CD4+ and CD8+ T cells contributes to T1D development, and that therapeutics targeting such signaling might be considered to counter T1D.